Structure, Functionality, and Active Release of Nanoclay–Soy Protein Films Affected by Clove Essential Oil - Echeverría, Ignacio (2016)
Nowadays, there is a pronounced interest in the potential use of biopolymer/layered silicate systems as active food packaging. This manuscript studied the effect of clove essential oil addition to soy protein–montmorillonite (MMT) films on the material’s structure, functionality, and active release. Active nanocomposite films were prepared by casting from aqueous dispersions containing soy protein isolates (SPI), glycerol, different concentrations of MMT and clove essential oil. Besides the important antioxidants and antimicrobial properties provided to nanocomposite films, the addition of clove essential oil exerted a plasticizing effect, which was verified in a decrease in the tensile strength and elastic modulus (up to 50 and 75 %, respectively) and an increase of the water content of films (up to 20 %). But the nanoclay caused a further strengthening effect in films containing CEO. While nanocomposite films containing 10 g MMT/100 g SPI reached an increase of 105 and 200 % in tensile strength and Young’s modulus, respectively, and a decrease of 340 % in their elongation at break, those that also contained CEO reached higher variations (230, 345, and 290 %, respectively). Clove essential oil presence also favored the exfoliation of montmorillonite into the soy protein matrix, while the nanoclay seemed to promote the release of active compounds, occasionally modifying the antimicrobial activity of films as well as the release of some of its Si and Al ions after being in contact with water (at least twice).